2021
DOI: 10.3390/antibiotics10020196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Antibiotic Prescribing for Common Infections in The Netherlands: A Primary Care-Based Observational Cohort Study

Abstract: In 2020, the COVID-19 pandemic brought dramatic changes in the delivery of primary health care across the world, presumably changing the number of consultations for infectious diseases and antibiotic use. We aimed to assess the impact of the pandemic on infections and antibiotic prescribing in Dutch primary care. All patients included in the routine health care database of the Julius General Practitioners’ Network were followed from March through May 2019 (n = 389,708) and March through May 2020 (n = 405,688).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 14 publications
(18 reference statements)
8
68
1
6
Order By: Relevance
“…While some similar ndings have been reported in recent studies from Scotland 6 , England 7 and the Netherlands 8 , that also found a reduction in both incidence of infectious diseases and antibiotic consumption in the general population, particularly in respiratory-tract infections and prescription of penicillins, our study, limited to children and adolescents, adds more detail about different pediatric age groups and covers a longer period of time that spans 2 lockdowns and intervening non-lockdown period during the pandemic. It evaluates data on ambulatory prescribing by GPs and hospital emergency services in a country which, in contrast to those which have previously reported, is in the "middle band' for usage of antibiotics, and shows comparable decreases to those seen in these "low-use" countries.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…While some similar ndings have been reported in recent studies from Scotland 6 , England 7 and the Netherlands 8 , that also found a reduction in both incidence of infectious diseases and antibiotic consumption in the general population, particularly in respiratory-tract infections and prescription of penicillins, our study, limited to children and adolescents, adds more detail about different pediatric age groups and covers a longer period of time that spans 2 lockdowns and intervening non-lockdown period during the pandemic. It evaluates data on ambulatory prescribing by GPs and hospital emergency services in a country which, in contrast to those which have previously reported, is in the "middle band' for usage of antibiotics, and shows comparable decreases to those seen in these "low-use" countries.…”
Section: Resultssupporting
confidence: 76%
“…[1][2][3][4] A sudden decrease in presentations of other pediatric infectious diseases was reported [1][2][3], and a reduction in antibiotic consumption in the general population was observed in some settings. [5][6][7] Inappropriate and widespread use of antibiotics is established as a main cause of emergence of resistant strains [8], with antimicrobial resistance (AMR) being recognized as a global public health threat.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in line with the findings of other international studies. Studies from the Netherlands [ 10 ] and the USA [ 11 , 12 ] have reported a decrease in presentation of infections and antibiotic prescribing in 2020 compared to previous year(s). However, the Dutch study [ 10 ] reported the highest decline in prescriptions for gastrointestinal infection, in contrast with the findings of our study that reported the highest decline for upper respiratory tract prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the Netherlands [ 10 ] and the USA [ 11 , 12 ] have reported a decrease in presentation of infections and antibiotic prescribing in 2020 compared to previous year(s). However, the Dutch study [ 10 ] reported the highest decline in prescriptions for gastrointestinal infection, in contrast with the findings of our study that reported the highest decline for upper respiratory tract prescriptions. Data from the USA reported the highest reduction in antibiotic prescribing in the outpatient setting in April (–39%) and May (–42%) 2020 compared to antibiotic prescribing in 2017–2019 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation